2022
DOI: 10.3389/fpls.2022.822136
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydraulic Failure in a Massive Mangrove Die-Off Event

Abstract: Between late 2015 and early 2016, more than 7,000 ha of mangrove forest died along the coastline of the Gulf of Carpentaria, in northern Australia. This massive die-off was preceded by a strong 2015/2016 El Niño event, resulting in lower precipitation, a drop in sea level and higher than average temperatures in northern Australia. In this study, we investigated the role of hydraulic failure in the mortality and recovery of the dominant species, Avicennia marina, 2 years after the mortality event. We measured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Mangroves have longer guard cell length for a given stomatal density than other vascular plants (Agduma et al ., 2022). Mangroves are confronted with increasing challenges for survival from global warming, which will result in dramatically increase in VPD, changes that may have led to dramatic die-off events in mangrove forests (Gauthey et al ., 2022). Yet, relatively little is known about the stomatal dynamics of mangroves in response to high VPD, information that would help us to understand the physiological response of mangroves following any hydraulic perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…Mangroves have longer guard cell length for a given stomatal density than other vascular plants (Agduma et al ., 2022). Mangroves are confronted with increasing challenges for survival from global warming, which will result in dramatically increase in VPD, changes that may have led to dramatic die-off events in mangrove forests (Gauthey et al ., 2022). Yet, relatively little is known about the stomatal dynamics of mangroves in response to high VPD, information that would help us to understand the physiological response of mangroves following any hydraulic perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, salinity is a primary hydrological driver, known to reduce soil water potential, limit root water uptake, increase the risk of xylem cavitation, and impair photosynthesis (Munns, 2002; Perri et al, 2019, 2022; Perri, Entekhabi, & Molini, 2018). A number of studies on mangrove biomass stocks and allometric relations have suggested that aridity and tidal inundation frequency, all‐controlling water salinity, are dominant limiting factors for coastal ecosystems' carbon storage (Adame et al, 2020; Bathmann et al, 2021; Gauthey et al, 2022; Rovai et al, 2021). These effects are analogous to those of water stress in terrestrial forests, and similarly to water stress, they could exert significant controls on species competition and canopy height (Klein et al, 2015; Koch et al, 2004).…”
Section: Introductionmentioning
confidence: 99%